CTNI-51. NEUROCOGNITIVE FUNCTION (NCF) OUTCOMES OF RTOG FOUNDATION 3508: A PHASE 3 TRIAL OF ABT-414 WITH CONCURRENT CHEMORADIATION AND ADJUVANT TEMOZOLOMIDE IN PATIENTS WITH EGFR-AMPLIFIED NEWLY DIAGNOSED GBM. (9th November 2020) - Wefel, Jeffrey S; Won, Minhee; Lassman, Andrew; Stern, Yaakov; Wang, Tony; Aldape, Kenneth; Armstrong, Terri; Vogelbaum, Michael; Sulman, Erik; Moazami, Golnaz; Macsai, Marian; Gilbert, Mark; et al.
Abstract: RTOG 3508/AbbVie M13-813/INTELLANCE-1 was a phase 3 trial of depatuximab-mafodotin (depatux-m, formerly ABT-414) that accrued 639 patients with EGFR-amplified newly diagnosed GBM. At the pre-specified interim OS analysis, the futility criteria were met and there was no survival benefit from adding depatux-m to SOC. Pre-specified secondary NCF analyses included time to decline in verbal learning and memory as assessed by the HVLT-R Total Recall based on the reliable change index. Exploratory NCF analyses examined changes in other HVLT-R outcomes over time. As corneal epitheliopathy causing visual impairment is a known toxicity of depatux-m, NCF tests that did not depend on visual acuity were employed. NCF testing occurred at baseline, day 1 of the first cycle of adjuvant depatux-m, every other cycle (i.e., 8 weeks) thereafter, and at progression. Compliance with test completion was 95% at screening and 80%, 70%, 58%, 51%, 47% thereafter through cycle 9. The most common reasons for missing data was site error. Time to HVLT-R Total Recall decline trended worse in the depatux-m arm compared to placebo but the difference was not significant (12 month deterioration: 41.2%, 95% CI: 3.50–47.2 vs 32.4%, 95% CI: 26.6- 38.4, p=0.052). The depatux-m arm, in comparison to the placebo arm, showed greater decline from baseline on the HVLT-R at the following time points: cycle 3 (Total Recall: mean= -1.8, SD=5.7 vs mean= -0.5, SD=5.5, respectively, p=0.046; Delayed Recall: mean= -1.1, SD=3.0 vs. mean= -0.2, SD=2.7, respectively, p=0.01), cycle 7 (Total Recall: mean= -0.6, SD=5.1 vs mean= 1.4, SD=5.0, respectively, p=0.009; Delayed Recall: mean -0.6, SD=3.0 vs. mean= 0.5, SD=2.7, respectively, p=0.01), and cycle 9 (Delayed Recall: mean=-0.4, SD=2.7 vs. mean= 0.8, SD=2.4, respectively, p=0.003). Depatux-m added to concurrent chemoradiation and adjuvant temozolomide was associated with faster time to deterioration and worse episodic learning and memory over time than placebo.